Skip to content
Related Articles

Related Articles

Improve Article

Class 12 RD Sharma Solutions – Chapter 29 The Plane – Exercise 29.6

  • Last Updated : 23 Jul, 2021
Geek Week

Question 1. Find the angle between the given planes:

(i) \vec{r} \cdot \left( 2 \hat{i} - 3 \hat{j} + 4 \hat{k} \right) = 1 and \vec{r} \cdot \left( - \hat{i}  + \hat{j}  \right) = 4

Solution:

Given 

\vec{r} \cdot \left( 2 \hat{i} - 3 \hat{j} + 4 \hat{k} \right) = 1 and \vec{r} \cdot \left( - \hat{i}  + \hat{j}  \right) = 4

As we know that the angle between the planes \vec{r} . \vec{n_1} = d_1 , \vec{r} . \vec{n_2} = d_2   is given by,

\cos \theta = \frac{\vec{n_1} . \vec{n_2}}{\left| \vec{n_1} \right| \left| \vec{n_2} \right|}



Here, \vec{n_1} = 2 \hat{i} - 3 \hat{j} + 4 \hat{k}, \vec{n_2} = - \hat{i} + \hat{j} + 0 \hat{k}

So, \cos \theta = \frac{\left( 2 \hat{i} - 3 \hat{j} + 4 \hat{k}  \right) . \left( - \hat{i}  + \hat{j}  + 0 \hat{k} \right)}{\left| 2 \hat{i}  - 3 \hat{j}  + 4 \hat{k}  \right| \left| - \hat{i} + \hat{j} + 0 \hat{k}  \right|}

\frac{- 2 - 3}{\sqrt{4 + 9 + 16} \sqrt{1 + 1 + 0}}

\frac{- 5}{\sqrt{29} \sqrt{2}}

\frac{- 5}{\sqrt{58}}

Therefore, \theta = \cos^{- 1} \left( \frac{- 5}{\sqrt{58}} \right)  .

(ii) \vec{r} \cdot \left( 2 \hat{i} - \hat{j}  + 2 \hat{k}  \right) = 6 and \vec{r} \cdot \left( 3 \hat{i}  + 6 \hat{j}  - 2 \hat{k}  \right) = 9

Solution:

Given 



\vec{r} \cdot \left( 2 \hat{i} - \hat{j}  + 2 \hat{k}  \right) = 6 and \vec{r} \cdot \left( 3 \hat{i}  + 6 \hat{j}  - 2 \hat{k}  \right) = 9

As we know that the angle between the planes \vec{r} . \vec{n_1} = d_1 , \vec{r} . \vec{n_2} = d_2   is given by,

\cos \theta = \frac{\vec{n_1} . \vec{n_2}}{\left| \vec{n_1} \right| \left| \vec{n_2} \right|}

Here, \vec{n_1} = 2 \hat{i} - \hat{j} + 2 \hat{k},\vec{n_2} = 3 \hat{i} + 6 \hat{j} - 2 \hat{k}

So, \cos \theta = \frac{\left( 2 \hat{i}- \hat{j} + 2 \hat{k}  \right) . \left( 3 \hat{i}  + 6 \hat{j} - 2 \hat{k}  \right)}{\left| 2 \hat{i} - \hat{j} + 2 \hat{k} \right| \left| 3 \hat{i} + 6 \hat{j} - 2 \hat{k}  \right|}

\frac{6 - 6 - 4}{\sqrt{4 + 1 + 4} \sqrt{9 + 36 + 4}}

\frac{- 4}{\left( 3 \right) \left( 7 \right)}

= -4/21

Therefore, θ = cos-1 (-4/21).

(iii) \vec{r} \cdot \left( 2 \hat{i} + 3 \hat{j}  - 6 \hat{k}  \right) = 5 and \vec{r} \cdot \left( \hat{i}  - 2 \hat{j}  + 2 \hat{k}  \right) = 9

Solution:



Given 

\vec{r} \cdot \left( 2 \hat{i} + 3 \hat{j}  - 6 \hat{k}  \right) = 5 and \vec{r} \cdot \left( \hat{i}  - 2 \hat{j}  + 2 \hat{k}  \right) = 9

As we know that the angle between the planes, \vec{r} . \vec{n_1} = d_1 , \vec{r} . \vec{n_2} = d_2   is given by,

\cos \theta = \frac{\vec{n_1} . \vec{n_2}}{\left| \vec{n_1} \right| \left| \vec{n_2} \right|}

Here, \vec{n_1} = 2 \hat{i} + 3 \hat{j} - 6 \hat{k} , \vec{n_2} = \hat{i} - 2 \hat{j}  + 2 \hat{k}

So, \cos \theta = \frac{\left( 2 \hat{i}  + 3 \hat{j}  - 6 \hat{k} \right) . \left( \hat{i}  - 2 \hat{j}  + 2 \hat{k}  \right)}{\left| 2 \hat{i}  + 3 \hat{j}  - 6 \hat{k}  \right| \left| \hat{i}  - 2 \hat{j}  + 2 \hat{k}  \right|}

\frac{2 - 6 - 12}{\sqrt{4 + 9 + 36} \sqrt{1 + 4 + 4}}

\frac{- 16}{\left( 7 \right) \left( 3 \right)}

= -16/21

Therefore, θ = cos-1 (-16/21).



Question 2. Find the angle between the planes:

(i) 2x − y + z = 4 and x + y + 2z = 3

Solution:

Given, 2x − y + z = 4 and x + y + 2z = 3

As we know that the angle between the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 is given by,

\cos \theta = \frac{a_1 a_2 + b_1 b_2 + c_1 c_2}{\sqrt{{a_1}^2 + {b_1}^2 + {c_1}^2} \sqrt{{a_2}^2 + {b_2}^2 + {c_2}^2}}

So, the angle between 2x – y + z = 4 and x + y + 2z = 3 is given by,

\cos \theta = \frac{\left( 2 \right) \left( 1 \right) + \left( - 1 \right) \left( 1 \right) + \left( 1 \right) \left( 2 \right)}{\sqrt{2^2 + \left( - 1 \right)^2 + 1^2} \sqrt{1^2 + 1^2 + 2^2}}

\frac{2 - 1 + 2}{\sqrt{4 + 1 + 1} \sqrt{1 + 1 + 4}}

\frac{3}{\sqrt{6} \sqrt{6}}

= 3/6

= 1/2



Therefore, θ = cos-1 (1/2) = π/3.

(ii) x + y − 2z = 3 and 2x − 2y + z = 5

Solution:

Given, x + y − 2z = 3 and 2x − 2y + z = 5

As we know that the angle between the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 is given by,

\cos \theta = \frac{a_1 a_2 + b_1 b_2 + c_1 c_2}{\sqrt{{a_1}^2 + {b_1}^2 + {c_1}^2} \sqrt{{a_2}^2 + {b_2}^2 + {c_2}^2}}

So, the angle between x + y – 2z = 3 and 2x – 2y + z = 5 is given by,

\cos \theta = \frac{\left( 1 \right) \left( 2 \right) + \left( 1 \right) \left( - 2 \right) + \left( - 2 \right) \left( 1 \right)}{\sqrt{1^2 + 1^2 + \left( - 2 \right)^2} \sqrt{2^2 + \left( - 2 \right)^2 + 1^2}}

\frac{2 - 2 - 2}{\sqrt{1 + 1 + 4} \sqrt{4 + 4 + 1}}

\frac{- 2}{\sqrt{6} \sqrt{9}}

= -2/3√6



Therefore, θ = cos-1 (-2/3√6).

(iii) x − y + z = 5 and x + 2y + z = 9

Solution:

Given, x − y + z = 5 and x + 2y + z = 9

As we know that the angle between the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 is given by,

\cos \theta = \frac{a_1 a_2 + b_1 b_2 + c_1 c_2}{\sqrt{{a_1}^2 + {b_1}^2 + {c_1}^2} \sqrt{{a_2}^2 + {b_2}^2 + {c_2}^2}}

So, the angle between x – y + z = 5 and x + 2y + z = 9 is given by,

\cos \theta = \frac{\left( 1 \right) \left( 1 \right) + \left( - 1 \right) \left( 2 \right) + \left( 1 \right) \left( 1 \right)}{\sqrt{1^2 + \left( - 1 \right)^2 + 1^2} \sqrt{1^2 + 2^2 + 1^2}}

\frac{1 - 2 + 1}{\sqrt{1 + 1 + 1} \sqrt{1 + 4 + 1}}

\frac{0}{\sqrt{3} \sqrt{6}}

= 0



Therefore, θ = cos-1 (0) = π/2.

(iv) 2x − 3y + 4z = 1 and − x + y = 4

Solution:

Given, 2x − 3y + 4z = 1 and − x + y = 4

As we know that the angle between the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 is given by,

\cos \theta = \frac{a_1 a_2 + b_1 b_2 + c_1 c_2}{\sqrt{{a_1}^2 + {b_1}^2 + {c_1}^2} \sqrt{{a_2}^2 + {b_2}^2 + {c_2}^2}}

So, the angle between 2x – 3y + 4z = 1 and -x + y + 0z = 4 is given by,

\cos \theta = \frac{\left( 2 \right) \left( - 1 \right) + \left( - 3 \right) \left( 1 \right) + \left( 4 \right) \left( 0 \right)}{\sqrt{2^2 + \left( - 3 \right)^2 + 4^2} \sqrt{\left( - 1 \right)^2 + 1^2 + 0^2}}

\frac{- 2 - 3 + 0}{\sqrt{4 + 9 + 16} \sqrt{1 + 1 + 0}}

\frac{- 5}{\sqrt{29} \sqrt{2}}

\frac{- 5}{\sqrt{58}}



Therefore, \theta = \cos^{- 1} \left( \frac{- 5}{\sqrt{58}} \right)  .

(v) 2x + y − 2z = 5 and 3x − 6y − 2z = 7

Solution:

Given, 2x + y − 2z = 5 and 3x − 6y − 2z = 7

As we know that the angle between the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 is given by,

\cos \theta = \frac{a_1 a_2 + b_1 b_2 + c_1 c_2}{\sqrt{{a_1}^2 + {b_1}^2 + {c_1}^2} \sqrt{{a_2}^2 + {b_2}^2 + {c_2}^2}}

So, the angle between 2x + y – 2z = 5 and 3x – 6y – 2z = 7 is given by,

\cos \theta = \frac{\left( 2 \right) \left( 3 \right) + \left( 1 \right) \left( - 6 \right) + \left( - 2 \right) \left( - 2 \right)}{\sqrt{2^2 + 1^2 + \left( - 2 \right)^2} \sqrt{3^2 + \left( - 6 \right)^2 + \left( - 2 \right)^2}}

\frac{6 - 6 + 4}{\sqrt{4 + 1 + 4} \sqrt{9 + 36 + 4}}

\frac{4}{\left( 3 \right) \left( 7 \right)}

= 4/21



Therefore, θ = cos-1 (4/21).

Question 3. Show that the following planes are at right angles.

(i) \vec{r} \cdot \left( 2 \hat{i} - \hat{j} + \hat{k}  \right) = 5 and \vec{r} \cdot \left( - \hat{i}  - \hat{j} + \hat{k}  \right) = 3

Solution:

Given, \vec{r} \cdot \left( 2 \hat{i} - \hat{j} + \hat{k}  \right) = 5 and \vec{r} \cdot \left( - \hat{i}  - \hat{j} + \hat{k}  \right) = 3

As we know that the planes \vec{r} . \vec{n_1} = d_1 , \vec{r} . \vec{n_2} = d_2   are perpendicular to each other only if \vec{n_1} . \vec{n_2} =0  .

Here, \vec{n_1} = 2 \hat{i} - \hat{j} + \hat{k} , \vec{n_2} = - \hat{i} - \hat{j} + \hat{k}

Now, we have

\vec{n_1} . \vec{n_2} = \left( 2 \hat{i}  - \hat{j}  + \hat{k}  \right) . \left( - \hat{i}  - \hat{j}  + \hat{k}  \right)

= -2 + 1 + 1 

= 0

So, the given planes are perpendicular.



Hence proved.

(ii) x − 2y + 4z = 10 and 18x + 17y + 4z = 49

Solution:

Given, x − 2y + 4z = 10 and 18x + 17y + 4z = 49

As we know that the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 are perpendicular to each other only if,

=> a1 a2 + b1 b2 + c1 c2 = 0

The given planes are x – 2y + 4z = 10 and 18x + 17y + 4z = 49.

Here, a1 = 1, b1 = – 2, c1 = 4, a2 = 18, b2 = 17 and c2 = 4

Now, we have

a1 a2 + b1 b2 + c1 c2 = (1) (18) + (- 2) (17) + (4) (4)

= 18 – 34 + 16 

= 0

So, the given planes are perpendicular.

Hence proved.

Question 4. Determine the value of λ for which the following planes are perpendicular to each other.

(i) \vec{r} \cdot \left( \hat{i}  + 2 \hat{j} + 3 \hat{k} \right) = 7 and \vec{r} \cdot \left( \lambda \hat{i} + 2 \hat{j}  - 7 \hat{k}  \right) = 26

Solution:

Given, \vec{r} \cdot \left( \hat{i}  + 2 \hat{j} + 3 \hat{k} \right) = 7 and \vec{r} \cdot \left( \lambda \hat{i} + 2 \hat{j}  - 7 \hat{k}  \right) = 26

As we know that the planes, \vec{r} . \vec{n_1} = d_1 , \vec{r} . \vec{n_2} = d_2   are perpendicular to each other only if,  \vec{n_1} . \vec{n_2} =0  .

Here, \vec{n_1} = \hat{i}| + 2 \hat{j} + 3 \hat{k} , \vec{n_2} = \lambda \hat{i} + 2 \hat{j} - 7 \hat{k}

The given planes are perpendicular. So, we have

\vec{n_1} . \vec{n_2} = 0

\left( \hat{i} + 2 \hat{j} + 3 \hat{k}  \right) . \left( \lambda \hat{i}  + 2 \hat{j} - 7 \hat{k}  \right) = 0



λ + 4 – 21 = 0

λ – 17 = 0

λ = 17

Therefore, the value of λ is 17.

(ii) 2x − 4y + 3z = 5 and x + 2y + λz = 5

Solution:

Given, 2x − 4y + 3z = 5 and x + 2y + λz = 5

As we know that the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 are perpendicular to each other only if,

=> a1 a2 + b1 b2 + c1 c2 = 0

The given planes are 2x – 4y + 3z = 5 and  x + 2y + λz = 5.

Here, a1 = 2, b1 = – 4, c1 = 3, a2 = 1, b2 = 2 and c2 = λ.

It is given that the given planes are perpendicular. So, we get

a1 a2 + b1 b2 + c1 c2 = 0

(2) (1) + (-4) (2) + (3) (λ) = 0

2 – 8 + 3λ = 0

3λ = 6

λ = 2

Therefore, the value of λ is 2.

(iii) 3x − 6y − 2z = 7 and 2x + y − λz = 5

Solution:

Given, 3x − 6y − 2z = 7 and 2x + y − λz = 5

As we know that the planes a1 x + b1 y + c1 z + d1 = 0 and a2 x + b2 y + c2 z + d2 = 0 are perpendicular to each other only if,

=> a1 a2 + b1 b2 + c1 c2 = 0

The given planes are 3x – 6y – 2z = 7 and 2x + y – λz = 5.

Here, a1 = 3, b1 = – 6, c1 = – 2, a2 = 2, b2 = 1 and c2 = -λ

Here, the given planes are perpendicular.

a1 a2 + b1 b2 + c1 c2 = 0

(3) (2) + (-6) (1) + (-2) (λ) = 0

6 – 6 + 2λ = 0

2λ = 0

λ = 0

Question 5. Find the equation of a plane passing through the point (−1, −1, 2) and perpendicular to the planes 3x + 2y − 3z = 1 and 5x − 4y + z = 5.

Solution:

The equation of any plane passing through  (-1, -1, 2) is,

a (x + 1) + b (y + 1) + c (z – 2) = 0  . . . . (1)

It is given that the above equation is perpendicular to each of the planes 3x + 2y – 3z = 1 and 5x – 4y + z = 5. 

3a + 2b – 3c = 0   . . . . (2)

5a – 4b + c = 0    . . . . (3)

On solving eq (1), (2) and (3), we get,

\begin{vmatrix}x + 1 & y + 1 & z - 2 \\ 3 & 2 & - 3 \\ 5 & - 4 & 1\end{vmatrix} = 0

-10 (x + 1) – 18 (y + 1) – 22 (z – 2) = 0

-5 (x + 1) – 9 (y + 1) – 11 (z – 2) = 0

5x + 5 + 9y + 9 + 11z – 22 = 0

5x + 9y + 11z – 8 = 0

Hence, the equation of the plane is 5x + 9y + 11z – 8 = 0

Question 6. Obtain the equation of the plane passing through the point (1, −3, −2) and perpendicular to the planes x + 2y + 2z = 5 and 3x + 3y + 2z = 8.

Solution:

The equation of any plane passing through (1, -3, -2) is,

a (x – 1) + b (y + 3) + c (z + 2) = 0 . . . . (1)

It is given that above equation is perpendicular to the planes x + 2y + 2z = 5 and 3x + 3y + 2z = 8.

a + 2b + 2c = 0    . . . . (2)

3a + 3b + 2c = 0  . . . . (3)

On solving eq (1), (2) and (3), we get,

\begin{vmatrix}x - 1 & y + 3 & z + 2 \\ 1 & 2 & 2 \\ 3 & 3 & 2\end{vmatrix} = 0

-2 (x – 1) + 4 (y + 3) – 3 (z + 2) = 0

-2x + 2 + 4y + 12 – 3z – 6 = 0

2x – 4y + 3z – 8 = 0

Hence, the equation of the plane is 2x – 4y + 3z – 8 = 0

Question 7. Find the equation of the plane passing through the origin and perpendicular to each of the planes x + 2y − z = 1 and 3x − 4y + z = 5.

Solution:

The equation of any plane passing through the origin (0, 0, 0) is,

a (x – 0) + b (y – 0) + c (z – 0) = 0  . . . . (1)

ax + by + cz = 0 

It is given that above equation is perpendicular to the planes x + 2y – z = 1 and 3x – 4y + z = 5 .

a + 2b – c = 0   . . . . (2)



3a – 4b + c = 0  . . . . (3)

On solving eq(1), (2) and (3), we get,

\begin{vmatrix}x & y & z \\ 1 & 2 & - 1 \\ 3 & - 4 & 1\end{vmatrix} = 0

– 2x – 4y – 10z = 0

x + 2y + 5z = 0

Hence, the equation of the plane is x + 2y + 5z = 0

Question 8. Find the equation of the plane passing through the points (1, −1, 2) and (2, −2, 2) and which is perpendicular to the plane 6x − 2y + 2z = 9.

Solution:

The equation of any plane passing through (1, -1, 2) is,

a (x – 1) + b (y + 1) + c (z – 2) = 0  . . . . (1)

It is given that above equation is passing through (2, -2, 2). So,

a (2 – 1) + b (-2 + 1) + c (2 – 2) = 0 

a – b = 0  . . . . (2)

It is given that above equation is perpendicular to the plane 6x – 2y + 2z = 9. So,

6a – 2b + 2c = 0

3a – b + c = 0  . . . . (3)

On solving eq(1), (2) and (3), we get,

\begin{vmatrix}x - 1 & y + 1 & z - 2 \\ 1 & - 1 & 0 \\ 3 & - 1 & 1\end{vmatrix} = 0

-1 (x – 1) – 1 (y + 1) + 2 (z – 2) = 0

– x + 1 – y – 1 + 2z – 4 = 0

x + y – 2z + 4 = 0

Hence, the equation of the plane is x + y – 2z + 4 = 0

Question 9. Find the equation of the plane passing through the points (2, 2, 1) and (9, 3, 6) and perpendicular to the plane 2x + 6y + 6z = 1.

Solution:

The equation of any plane passing through (2, 2, 1) is,

a (x – 2) + b (y – 2) + c (z – 1) = 0  . . . . (1)

It is given that the above equation is passing through (9, 3, 6). So,

a (9 – 2) + b (3 – 2) + c (6 – 1) = 0

7a + b + 5c = 0  . . . . (2)

It is given that the above equation is perpendicular to the plane 2x + 6y + 6z = 1. So,

2a + 6b + 6c = 0

a + 3b + 3c = 0 . . . . (3)

On solving eq(1), (2) and (3), we get

\begin{vmatrix}x - 2 & y - 2 & z - 1 \\ 7 & 1 & 5 \\ 1 & 3 & 3\end{vmatrix} = 0

-12 (x – 2) – 16 (y – 2) + 20 (z – 1) = 0

3 (x – 2) + 4 (y – 2) – 5 (z – 1) = 0

3x + 4y – 5z = 9

Hence, the equation of the plane is 3x + 4y – 5z = 9

Question 10. Find the equation of the plane passing through the points whose coordinates are (−1, 1, 1) and (1, −1, 1) and perpendicular to the plane x + 2y + 2z = 5.

Solution:

The equation of any plane passing through (-1, 1, 1) is,

a (x + 1) + b (y – 1) + c (z – 1) = 0  . . . . (1)

It is given that the above equation passed through (1, -1, 1). So,

a (1 + 1) + b (-1 – 1) + c (1 – 1) = 0 

2a – 2b = 0  . . . . (2)

It is given that the above equation is perpendicular to the plane x + 2y + 2z = 5. So,

a + 2b + 2c = 0  . . . . (3)

On solving eq(1), (2) and (3), we get

\begin{vmatrix}x + 1 & y - 1 & z - 1 \\ 2 & - 2 & 0 \\ 1 & 2 & 2\end{vmatrix} = 0

-4 (x + 1) – 4 (y – 1) + 6 (z – 1) = 0

2 (x + 1) + 2 (y – 1) – 3 (z – 1) = 0

2x + 2y – 3z + 3 = 0

Hence, the equation of the plane is 2x + 2y – 3z + 3 = 0



Question 11. Find the equation of the plane with intercept 3 on the y-axis and parallel to the ZOX plane.

Solution:

The equation of the plane parallel to the plane ZOX  is,

y = b  . . . . (1)

According to the question, it is given that this plane passes through (0, 3, 0). So,

=> b = 3

On substituting this value in eq(1), we get

y = 3, 

Hence, the equation of the plane is

y = 3 

Question 12. Find the equation of the plane that contains the point (1, −1, 2) and is perpendicular to each of the planes 2x + 3y − 2z = 5 and x + 2y − 3z = 8.

Solution:

The equation of any plane passing through (1, -1, 2) is,

a (x – 1) + b (y + 1) + c (z – 2) = 0  . . . . (1)

It is given that the above equation is perpendicular to the plane 2x + 3y – 2z = 5. So, 

2a + 3b – 2c = 0  . . . . (2)

It is given that the above equation is perpendicular to the plane x + 2y – 3z = 8. So,

a + 2b – 3c = 0   . . . . (3)

So, on solving eq (1), (2) and (3), we get

\begin{vmatrix}x - 1 & y + 1 & z - 2 \\ 2 & 3 & - 2 \\ 1 & 2 & - 3\end{vmatrix} = 0

-5 (x – 1) + 4 (y + 1) + 1 (z – 2) = 0

5x – 4y – z = 7

Hence, the equation of the plane is 5x – 4y – z = 7

Question 13. Find the equation of the plane passing through (a, b, c) and parallel to the plane \vec{r} \cdot \left( \hat{i}  + \hat{j}  + \hat{k}  \right)  = 2.

Solution:

Given equation of the plane is \vec{r} \cdot \left( \hat{i}  + \hat{j}  + \hat{k}  \right)  = 2

So, on substituting \vec{r} = x \hat{i} + y \hat{j} + z \hat{k}  in the given equation of the plane, we get

\left( x \hat{i}  + y \hat{j}  + z \hat{k}  \right) . \left( \hat{i}  + \hat{j}  + \hat{k}  \right) = 2

=> x + y + z – 2 = 0   . . . . (1)

The equation of a plane which is parallel to plane (eq 1) is of the form,

x + y + z = k   . . . . (2)

It is given that above equation of plane is passing through the point (a, b, c). So,

a + b + c = k

On substituting this value of  k in eq(2), we get

x + y + z = a + b + c

Hence, the equation of the plane is

x + y + z = a + b + c 

Question 14. Find the equation of the plane passing through the point (−1, 3, 2) and perpendicular to each of the planes x + 2y + 3z = 5 and 3x + 3y + z = 0.

Solution:

The equation of any plane passing through point (-1, 3, 2) is,

a (x + 1) + b (y – 3) + c (z – 2) = 0  . . . . (1)

It is given that the above equation is perpendicular to the plane x + 2y + 3z = 5. So, 

a + 2b + 3c = 0   . . . . (2)

It is given that the above equation is perpendicular to the plane 3x + 3y + z = 0. So,

3a + 3b + c = 0   . . . . (3)

On solving eq (1), (2) and (3), we get

\begin{vmatrix}x + 1 & y - 3 & z - 2 \\ 1 & 2 & 3 \\ 3 & 3 & 1\end{vmatrix} = 0

-7 (x + 1) + 8 (y – 3) – 3 (z – 2) = 0

7x – 8y + 3z + 25 = 0

Hence, the equation of the plane is

7x – 8y + 3z + 25 = 0

Question 15. Find the vector equation of the plane through the points (2, 1, −1) and (−1, 3, 4) and perpendicular to the plane x − 2y + 4z = 10. 

Solution:

The equation of any plane passing through (2, 1, -1) is,

a (x – 2) + b (y – 1) + c (z + 1) = 0  . . . . (1)



It is given that the above equation passes through (-1, 3, 4). So,

a (-1 – 2) + b (3 – 1) + c (4 + 1) = 0

-3a + 2b + 5c   . . . . (2)

It is given that the above equation is perpendicular to the plane x – 2y + 4z = 10. So,

a – 2b + 4c = 0  . . . . (3)

On solving eq (1), (2) and (3), we get

\begin{vmatrix}x - 2 & y - 1 & z + 1 \\ - 3 & 2 & 5 \\ 1 & - 2 & 4\end{vmatrix} = 0

18 (x – 2) + 17 (y – 1) + 4 (z + 1) = 0

18x + 17y + 4z – 49 = 0

Hence, the equation of the plane is

18x + 17y + 4z – 49 = 0

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the  Demo Class for First Step to Coding Course, specifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.




My Personal Notes arrow_drop_up
Recommended Articles
Page :